Can early golfing lead to acetabular and lower limb changes? A cross-sectional study. Issue 1 (February 2023) - Prum, Grégoire; Sauret, Christophe; Bourgain, Maxime; Rouillon, Olivier; Rouch, Philippe; Thoreux, Patricia
Golf is a sport which is sometimes started early, in particular for players who become professionals. The combination of an early practice (before growth peak) with high training loads could further increase the occurrence of musculoskeletal injuries. The aim of this study was to comparing the morphological and positional parameters of the acetabular and lower limbs of golfers with early or late involvement in the golf practice. Two populations: golfers with early involvement in golf practice (before adolescent growth peak, 12 y.o.), golfers with late involvement (after adolescent growth peak). Subjects underwent a low-dose biplanar radiograph in standard standing position allowing the 3D reconstruction of bones. Morphological parameters were automatically computed from it. Thirty-five male golf players were included: 13 in early group (mean age 27 y.o.), 22 in late group (mean age 56 y.o.). The index of cumulative torsions (sum of the tibial and femoral torsions) was different between sides in early: 7° on the lead-side; 20° on the trail-side ( p < 0.01). This index was different between the lead-side of the early group compared to late (22°; p < 0.001). It could be explained by the mechanical stresses applied on lead knee and ankle during the follow-through. Intensive golf involvement by young players could lead to bone morphology modifications.